2007
DOI: 10.1080/14017430601085948
|View full text |Cite
|
Sign up to set email alerts
|

Functional and phenotypic changes in polymorphonuclear neutrophils induced by catecholamines

Abstract: The effect of catecholamines on the expression of CD 62 l explains the increased expression of L-selection on PMN observed after trauma. The suppression of CD 11 b reduces leukocyte adherence and consecutive abnormalities in microvascular flow. Epinephrine inhibits the generation of oxidative free radicals by PMN with potentially detrimental effects with respect to bacterial clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…CD18 (CD11b/CD18, Mac-1, ␤2-integrin) is a membrane adherence protein subunit found on PMN membranes that have been activated for migration. 8,10,15,32 These PMN membrane receptors bind to endothelial receptors during migration, initiating one of the earliest steps in the inflammatory reaction. It has been reported that there was an increased expression of the CD11b/ CD18 complex on neutrophils from young polytrauma patients (ISS Ͼ 16), 33 but to our knowledge, CD18 expression has not been reported in elder trauma patients.…”
Section: Neutrophil Cd18 Expressionmentioning
confidence: 99%
“…CD18 (CD11b/CD18, Mac-1, ␤2-integrin) is a membrane adherence protein subunit found on PMN membranes that have been activated for migration. 8,10,15,32 These PMN membrane receptors bind to endothelial receptors during migration, initiating one of the earliest steps in the inflammatory reaction. It has been reported that there was an increased expression of the CD11b/ CD18 complex on neutrophils from young polytrauma patients (ISS Ͼ 16), 33 but to our knowledge, CD18 expression has not been reported in elder trauma patients.…”
Section: Neutrophil Cd18 Expressionmentioning
confidence: 99%
“…It can be suggested that PMAN reduction during chronic treatment with OPC can be mediated by activation of the hypothalamic-pituitary-adrenal system [13]. PMAN reduction can be related to inhibition of cytosol esterases in monocyte phagocytic system (α-naphthyl acetate esterase, α-naphthyl butyra te esterase, α-naphthyl-AS-D-acetate esterase, and α-na phthyl-AS-D-chloracetate esterase) [3], and to initiation of LPO with OPC [3].…”
Section: Resultsmentioning
confidence: 99%
“…The concentration (2-100 ng/mL) used in our study is generally within the physiologic range in animals. Previous studies have demonstrated that exogenous NE exerts immunostimulatory effects on macrophages at low concentrations, but it exerts immunosuppressive effects at high concentrations [10,11]. In order to elucidate the direct modulation of physiological NE on macrophage function, we treated murine macrophages with exogenous NE, which simulate the in vivo role of NE in acute stress.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in phagocytosis, reactive oxygen production, and chemotaxis have been shown in macrophages isolated from appropriate exercise in humans and animals [8,9]. Previous in vitro studies have further revealed that low concentrations of NE exert immunostimulatory effects on macrophage in the presence of bacterial lipopolysaccharide (LPS), while high concentrations exert immunosuppressive effects [10,11]. Therefore, the role of endogenous NE may be distinct from the effects of therapeutic concentrations of norepinephrine.…”
Section: Introductionmentioning
confidence: 96%